Edukasi Tentang Jamur Sagu dan Konservasinya Bagi Siswa SD di Kampung Kehiran Kabupaten Jayapura - Sufaati, Supeni; Budi, I Made; Rahayu, Irma; Ramandey, Erlies P. (Bakti Hayati: Jurnal Pengabdian Indonesia, 2024)
The local people of Kehiran Village are heavily reliant on a sustainable harvesting of sago mushrooms from the surrounding forest; this not only provides them with a source of income, but sustenance too. In order to preserve this invaluable knowledge, it is imperative to educate the younger generation on the morphology, nutritional value and beneficial effects that sago mushrooms offer. This can be achieved through educational programmes for elementary school students in Kehiran Village, which should include information on the importance of conservation and habitat protection. This educational initiative was conducted at SDN Inpres Kehiran in Jayapura Regency from June to September 2024, utilising a multifaceted approach encompassing lectures, focus group discussions, participatory planning, and hands-on practicals.The programme met with remarkable success, surpassing initial expectations, largely due to the enthusiastic participation of the students and the instrumental role played by the Principal and teaching staff in its seamless execution.